Keaktifan Mahasiswi Selama Kuliah Daring - -, Maftucha (PSGA LP2M IAIN Pontianak, 2023)
The outbreak of Coronavirus throughout the earth has shaken up all aspects of life, including the world of Education. By quick and appropriate steps, the government finally made a policy to implement online learning. This article used a mixed-method with a phenomenological approach. The study objects were 240 students of IAIN Tulungagung. The results showed that there are significant differences between male and female students in running the online-class learning activities. This is proven by various indicators such as First, female students are more active in contributing to discussions; Second, female students are more creative and better in completing the assignments as well as mastering the materials; Third, female students are more explorative in finding references throughout the internet. The increasing number of women in the world of Education as well as their quality may provide positive energy toward the development of the nation.